Coupling effects of water content, temperature, oxygen density, and polytetrafluoroethylene loading on oxygen transport through ionomer thin film on platinum surface in catalyst layer of proton exchange membrane fuel cell. (19th January 2022) - Zhang, Xiao-Meng; Li, Qing-Gang; Si, Chao; Zhong, Ying-Jie; Wang, Xiao-Dong; Jiao, Long; Deng, Kai; Wang, Yu-Lin; Liu, Qiu-Xiang; Xia, Yu-Zhen
Abstract: In this work, coupling effects of water content, temperature, oxygen density, and polytetrafluoroethylene (PTFE) loading on oxygen transport through an ionomer thin film on a platinum surface in a catalyst layer of a proton exchange membrane (PEM) fuel cell are investigated using molecular dynamics approach. Taguchi orthogonal algorithm is employed to comprehensively analyze the coupling effects in a limited number of cases. It is found that the effect of operation temperature is the weakest among the four factors, which has the smallest effect index 14.4. Coupling effects including the PTFE loadings on the oxygen transfer through the ionomer thin film is uncovered. Less PTFE loadings should be beneficial for the oxygen transfer. The chemical potential gradient is considered as the major driven force for the oxygen transport through the ionomer thin film, and oxygen density is the dominating factor, significantly affecting the chemical potential in the thin film. Graphical abstract: Image 1 Highlights: MD approach is used simulate the nano-scale oxygen mass transfer process in CLs. A system composed by a Pt surface covered by a layer of ionomer is built. Taguchi algorithm is applied to study effects of four controlled parameters. Oxygen density plays the most important role in oxygen transport. Concentration polarization is of minor importance for the oxygen transport.